The degree of effectiveness for teaching practical courses by distance learning from the principals’ point of view of secondary vocational schools in the directorate of Jerusalem - Bselih, Intesar Majed; Shuibat, Mohammad Awad (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed at identifying the degree of effectiveness for teaching practical courses by distance learning from the principals’ point of view of secondary vocational schools in the directorate of Jerusalem during the Covid-19 pandemic. This study used the quantitative method with a five Likert-scale questionnaire to collect data that had three major fields. The study was conducted on a population of seven vocational schools’ principals. The results of the study revealed that the total average is (3.43 from 5) with a medium degree of effectiveness, and the averages of the fields were respectively, (3.57), (3.43), and (3.29) for the field understanding the practical skills, used computer applications, and virtual classroom management with a medium degree of effectiveness. The study recommended that it is necessary to train teachers to acquire the virtual classroom management skills, and to establish a specialized workshops equipped with high quality tools and instruments as well as multimedia systems to enable the students to learn the practical skills.
Keywords: the effectiveness of distance learning; Covid-19; practical courses; the evaluation of the vocational school principals; directorate of Jerusalem